Defect in serine 46 phosphorylation of p53 contributes to acquisition of p53 resistance in oral squamous cell carcinoma cells - Arief Ichwan, Solachuddin Jauhari; Shumpei, Yamada; Piyamas, Sumrejkanchanakij; Elza, Ibrahim-Auerkari,; K, Eto; Ikeda, Masa-Aki (Nature, 2006)
To investigate whether dysregulation of p53 phosphorylation confers tumor resistance to p53, we analysed the effects of wild-type p53 on oral squamous cell carcinoma(SCC) cell lines carrying various mutations of p53. Introduction of exogenous p53 neither induced apoptosis nor suppressed colony formation in HSC-3 cells lacking any detectable p53 and HSC-4 cells expressing mutant p53R248Q protein. Consistently, exogenous p53 did not induce proapoptotic p53-target genes in these p53-resistant cells. We found that phosphorylation of exogenous p53 on serine 46 (Ser46) was severely impaired in HSC-3 but not HSC-4 cells. A mutant mimicking Ser46-phosphorylation (p53S46D) enhanced proapoptotic Noxa promoter activity, and overcame the resistance to p53-mediated apoptosis and growth suppression in HSC-3 cells. Conversely, a mutant defective for Ser46-phosphorylation(p53S46A) failed to suppress the growth of p53-sensitive HSC-2 cells. In contrast to HSC-3 cells, p53S46D had no effect on HSC-4 cells, and inhibition of endogenous p53R248Q by siRNA restored p53- mediated apoptosis in HSC-4 cells, indicating a dominant- negative effect of p53R248Q protein on wild-type p53 function. These results demonstrate that the defect in Ser46 phosphorylation accounts for the p53 resistance of HSC-3 cells, and provide evidence for a mechanism underlying the acquisition of p53 resistance in oral SCC.